2020
DOI: 10.2147/jmdh.s279092
|View full text |Cite
|
Sign up to set email alerts
|

<p>Interprofessional Cooperation: An Interventional Study Among Saudi Healthcare Teaching Staff at King Saud University</p>

Abstract: Background Collaborative interprofessional practice improves health outcomes. Interprofessional education (IPE) is essential in improving this collaboration and the quality of care. Although the majority of IPE research focuses on students, the delivery of IPE requires multiple levels of support within educational institutions, particularly teaching staff that are positive about and advocate for IPE. This study explored the attitudes of teaching staff towards interprofessional collaboration across… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 30 publications
0
7
0
1
Order By: Relevance
“…Interprofessional collaboration dapat diajarkan sejak para tenaga kesehatan masih di tingkat pendidikan (27) atau interprofessional education (IPE) (13), hal ini perlu adanya dukungan dari institusi pendidikan kesehatan (21). Para mahasiswa antar disiplin yang berbeda akan berinteraksi dan bekerjasama satu dengan yang lain, dapat meningkatkan kreativitas, meningkatkan kepercayaan diri dan adanya kepuasan antar tenaga kesehatan sehingga diharapkan mampu menyelesaikan masalah pasien, sehingga mereka akan memiliki pengalaman ketika mereka nanti bekerja di tempat pelayanan kesehatan (14).…”
Section: Discussionunclassified
“…Interprofessional collaboration dapat diajarkan sejak para tenaga kesehatan masih di tingkat pendidikan (27) atau interprofessional education (IPE) (13), hal ini perlu adanya dukungan dari institusi pendidikan kesehatan (21). Para mahasiswa antar disiplin yang berbeda akan berinteraksi dan bekerjasama satu dengan yang lain, dapat meningkatkan kreativitas, meningkatkan kepercayaan diri dan adanya kepuasan antar tenaga kesehatan sehingga diharapkan mampu menyelesaikan masalah pasien, sehingga mereka akan memiliki pengalaman ketika mereka nanti bekerja di tempat pelayanan kesehatan (14).…”
Section: Discussionunclassified
“…Despite the fact that students in our study and in similar studies [18][19][20][21] had high readiness for IPE, faculty members reported several barriers to implementing IPE. According to Bashatah et al, 22 IPE implementation is often hampered by a lack of technical assistance; time restrictions; a lack of administrative support and training; a lack of appreciation; and difficulties in forming collaborative partnerships, such as siloed curricula and calendars. In addition, faculty members have limited insight into each other's professions.…”
Section: Discussionmentioning
confidence: 99%
“… 21 Therefore, the deanship of skills development launched different initiatives to assess faculty members’ willingness from various healthcare colleges to adopt and implement IPE. 20 Moreover, the students’ perspective regarding the use of IPE in teaching different clinical case scenarios was deemed instrumental in the success of any future IPE course. Thus, the university has recently launched an interprofessional competition between students from different healthcare colleges during the COVID-19 pandemic to explore the benefits and challenges of introducing a new virtual IPE course for healthcare students.…”
Section: Methodsmentioning
confidence: 99%
“…In Saudi Arabia, the IPE in healthcare education is largely absent despite the familiarity of IPE by many faculty members in various healthcare colleges, and the willingness of many to include IPE as an integral part of the undergraduate healthcare curricula as suggested by a recently published study. 20 Therefore, a group of healthcare faculty members decided to explore the feasibility of implementing IPE during the COVID-19 pandemic by conducting a competition among students from various healthcare colleges to encourage them to participate and collaborate due to the lack of exposure to IPE for most students in the healthcare colleges in Saud Arabia.…”
Section: Introductionmentioning
confidence: 99%